Influence of grooved rib tip structure on tip loss and heat transfer in a gas turbine blade - Kong, Zhiqi; Zhang, Tianyi; Du, Wei (Frontiers in Energy Research, 2022)
This study focuses on the effects of three groove tip structures (full rib groove tip, partial rib tip on the suction side, and partial rib tip on the pressure side) on tip leakage flow, aerodynamic characteristics of a cascade, and heat transfer in a gas turbine blade. The groove’s width B = 1.6 mm, while the tip clearance is τ = 1.2 mm. Results of the flow parameters, fluid flow, and heat transfer in the recessed channel are discussed. The results show that all ribbed tips obtain more uniform outlet flow angle distribution and higher aerodynamic performance than the plane tips. The total aerodynamic pressure loss of the ribbed tips on the pressure side is the same as that of complete ribbed tips. The evolution mechanisms are different, although both can improve the turbine efficiency. Although the partial rib tip on the pressure side weakens the mixing of the channel vortex and leakage vortex near the trailing edge and has the best control effect on the leakage vortex, the lack of the suction side rib will make it easier for the low-energy fluid to flow into the gap from the front of the suction side, which is not conducive to reducing the leakage flow inside the gap; the full rib tip not only minimizes the tip relative leakage flow and leakage loss but also increases the channel vortex loss. With the complex vortex system in the groove and the rib blocking effect at the leakage outlet, the suction-side rib tip becomes the tip structure with the best leakage flow control effect under the same clearance, but the leakage vortex loss is the highest.